Numerical Simulation of Sintering of Non-equal Metal Powders by Surface Diffusion. Issue 10 (October 2017) - Min, Song; Zhoushun, Zheng; Dongdong, Chen; Huiping, Tang; Jianzhong, Wang
Abstract: This paper focuses on the numerical simulation of sintering of non-equal metal powders by surface diffusion. In order to simulate the sintering process of non-equal metal powders clearly, the surface diffusion model was modified by establishing more suitable initial boundary conditions. And this model was numerically solved by the finite difference method. The 2D and 3D numerical simulations of two metal powders with radii ratios of 1:1, 1:1.5, 1:2 were implemented by this model. Through comparison, the simulation results are consistent with the experimental ones. Finally, the effect of metal powders' radii ratios on the growth rate of sintering neck was investigated. The results show that the sintering neck radius increases with the decreasing of radii ratios of metal powders.